Experiences of resilience during the COVID-19 pandemic: A qualitative study among high and low socio-economic status individuals in the Netherlands - Kristina Thompson; Dani van der Kamp; Sarah Vader; Roald Pijpker; Lea den Broeder; Annemarie Wagemakers (Elsevier, 2023)
Resilience to adverse events is increasingly recognized as important for human health. Socio-economic status (SES) is also frequently identified as a predictor of resilience. However, it is not well-understood how people define resilience in their everyday lives, and whether individuals have different experiences of resilience based on their SES. This study sought to fill these gaps, in the context of the COVID-19 pandemic and pandemic mitigation policies in the Netherlands.We interviewed high (n = 38) and low (n = 37) SES participants about their understanding and experiences of resilience during this period. Participants took part in individual interviews and focus groups in September 2021. Transcripts were analyzed thematically.A key theme was coping with adversity, in line with commonly-used definitions of resilience. However, we found that resilience was often defined more broadly. Resilience also encompassed aspects of self-reflection and improvement, and faith in oneself, the community and the nation. There were also key differences by SES background: elaborate and optimistic definitions and experiences of resilience were more often described by high SES individuals. For instance, high SES participants more frequently defined resilience as growing and improving. In contrast, low SES participants more commonly experienced resilience as enduring until better times arrived.Having a higher SES seemed to support resilience during the COVID-19 pandemic. This indicates that adverse events may exacerbate pre-existing financial and material difficulties among low SES individuals. This finding underscores the importance of addressing financial precarity prior to adverse events.